ASSIST - Patient satisfaction survey in postoperative pain management from Indian subcontinent - Balavenkata Subramanian; Naman Shastri; Lutful Aziz; Ramachandran Gopinath; Anil Karlekar; Yatin Mehta; Anand Sharma; Jitendra Suhas Bapat; Pradeep Jain; Aveek Jayant; Tanvir Samra; Ajantha Perera; et al. (Wolters Kluwer Medknow Publications, 2017)
Introduction: To compare pain scores at rest and ambulation and to assess patient satisfaction between the different modalities of pain management at different time points after surgery. Settings and Design: The ASSIST (Patient Satisfaction Survey: Pain Management) was an investigator-initiated, prospective, multicenter survey conducted among 1046 postoperative patients from India. Material and Methods: Pain scores, patient's and caregiver's satisfaction toward postoperative pain treatment, and overall pain management at the hospital were captured at three different time points through a specially designed questionnaire. The survey assessed if the presence of acute pain services (APSs) leads to better pain scores and patient satisfaction scores. Statistical Analysis: One-way ANOVA was used to evaluate the statistical significance between different modalities of pain management, and paired t-test was used to compare pain and patient satisfaction scores between the APS and non-APS groups. Results: The results indicated that about 88.4% of patients reported postoperative pain during the first 24 h after surgery. The mean pain score at rest on a scale of 1-10 was 2.3 ± 1.8 during the first 24 h after surgery and 1.1 ± 1.5 at 72 h; the patient satisfaction was 7.9/10. Significant pain relief from all pain treatment was reported by patients in the non-APS group (81.6%) compared with those in the APS (77.8%) group (P < 0.0016). Conclusion: This investigator-initiated survey from the Indian subcontinent demonstrates that current standards of care in postoperative pain management remain suboptimal and that APS service, wherever it exists, is yet to reach its full potential.